Integrate Social Justice Into the Mathematics Curriculum in Learning - Abtahi, Micayla; Battell, Catherine (Jurnal Ilmiah Peuradeun, 2017)
Although concerns for equity have become ever more central within mathematics education, there is still little consensus on how the term should be defined or how to effectively work towards equity in classroom learning. Equity initiatives that rely solely on arguments about achievement gaps can be dangerous, as they can perpetuate deficit notions of marginalized students and position dominant groups as the norm to which others should aspire. The project is analyzed using Marilyn Cochran-Smith’s six principles of pedagogy for teaching for social justice. In the study group, teachers were involved in designing research projects to honour their students’ cultural and community knowledge and to develop mathematics teaching with a social justice focus. We offer three examples of teaching mathematics for social justice in diverse classrooms, and consider the broader implications of inquiry projects such as these. While we and the teachers came together as a group because of a shared interest in using a social justice approach to mathematics teaching. We found that the study group process ended up emphasizing some aspects of teaching for social justice – in particular, bringing social justice issues explicitly into the curriculum, building on student interests and experiences, and working with families and community.